Pengembangan Kelompok Bimbingan Belajar (Bimbel) Berbasis Organisasi IPNU dan IPPNU Di Desa Kenanti Kecamatan Dukuhseti Kabupaten Pati: Development of IPNU and IPPNU Organization-Based Tutoring Groups (Bimbel) in Kenanti Village, Dukuhseti District, Pati Regency - Zamroni, Edris; Gudnanto, Gudnanto (PADIMAS Jurnal Pengabdian Masyarakat, 2023)
The existence of tutoring institutions in Indonesia certainly does not violate existing laws and instead has a strong legal basis in terms of the Education Law. In relation to the implementation of the educational process in Indonesia, the existence of this institution is very helpful for parents of students (SD, SMP and SMA) who want their children to excel in school. Indeed, there are many views in the field that teachers are less or not successful in providing an optimal educational process for students so that students can understand. Therefore, most parents rely on tutoring institutions to improve their children's performance at school. In Kenanti Village there are around 1244 students who have the potential to become tutoring participants. However, there is not a single tutoring institution in the village or in its surroundings. The tutoring group will work with IPNU and IPPNU as the basis for activities. This training and development will be carried out in 10 planned activities starting from identifying the eligibility of prospective tutors to training on basic skills in teaching strategies for students participating in tutoring activities. The mentoring and training activities for the development of Tutoring Institutions are carried out from 12 October 2021 – 4 January 2022. The result IPNU and IPPNU-based RULI Tutoring Institute was formed in Kenanti Village, Dukuhseti District, Pati Regency.